2005
DOI: 10.1086/502546
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Hand Drying for Removing Bacteria From Washed Hands Comparison of Paper Towel Drying With Warm Air Drying

Abstract: Holding hands stationary and not rubbing them was desirable for removing bacteria. Ultraviolet light reinforced the removal of bacteria during warm air drying. Paper towels were useful for removing bacteria from fingertips but not palms and fingers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 16 publications
(5 reference statements)
2
44
0
3
Order By: Relevance
“…39 In many instances, however, rubbing hands with hot air dryers to hasten drying would only lead to greater bacterial numbers and airborne dissemination. 49 It might be that rubbing hands causes bacteria to migrate from the hair follicles to the skin surface. 35,44 Many studies have found friction to be a key component in hand drying for removing contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In many instances, however, rubbing hands with hot air dryers to hasten drying would only lead to greater bacterial numbers and airborne dissemination. 49 It might be that rubbing hands causes bacteria to migrate from the hair follicles to the skin surface. 35,44 Many studies have found friction to be a key component in hand drying for removing contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al 49 used a contact plate method to evaluate the effect of hot air dryers when hands were rubbed and when hands were held stationary. When hands were rubbed, bacteria on the hands increased significantly after 15 seconds of use.…”
Section: Removal Of Bacteriamentioning
confidence: 99%
“…Hautpflegemittel Konventionelle Heißlufttrockner sind für Gesundheitseinrichtungen ungeeignet, weil die Trocknungswirkung im Vergleich zum Handtuch geringer ist [221][222][223]. Nur "jet air" Händetrockner mit Infrarot erwiesen sich bei 10 s Anwendung dem Papierhandtuch in der Trocknungswirkung gleichwertig [224].…”
Section: Ausstattung Medizinischer Handwaschplätzeunclassified
“…257 In a comparison of methods to test the efficiency of hand drying for the removal of bacteria from washed hands, warm air drying performed worse than drying with paper towels. 258 This is in contrast to another study, which found warm air dryers to be the most efficient when compared with paper and cloth towels. 257 However, air dryers may be less practical because of the longer time needed to achieve dry hands, 258 with a possible negative impact on hand hygiene compliance.…”
Section: Hand Dryingmentioning
confidence: 64%